2021
DOI: 10.1002/jobm.202100209
|View full text |Cite
|
Sign up to set email alerts
|

Cold‐active catalase from the psychrotolerant fungus Penicillium griseofulvum

Abstract: Cold-active catalase (CAT) elicits great interest because of its vast prospective at the medical, commercial, and biotechnological levels. The study paper reports the production of cold-active CAT by the strain Penicillium griseofulvum P29 isolated from Antarctic soil. Improved enzyme production was achieved by optimization of medium and culture conditions. Maximum CAT was demonstrated under low glucose content (2%), 10% inoculum size, temperature 20°C, and dissolved oxygen concentration (DO) 40%. An effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Both antioxidant enzymes degrade • O2 − and H 2 O 2 , respectively, the generation of which is accelerated under stress conditions. Increased activity of antioxidant enzymatic defense is one of the main characteristics of stress caused by low temperatures [33,55]. ROS plays a role in cell signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both antioxidant enzymes degrade • O2 − and H 2 O 2 , respectively, the generation of which is accelerated under stress conditions. Increased activity of antioxidant enzymatic defense is one of the main characteristics of stress caused by low temperatures [33,55]. ROS plays a role in cell signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Cat-2 from the mesophilic Serratia marcescens SYBC-01 isolated from Wuxi City, China, exhibits significant relative activity (73.8%) at 0 • C, and its ideal temperature is roughly 20 • C. The authors characterized this enzyme as a type of cold-adaptive enzyme [30]. Krumova et al (2021) reported CA CAT produced by a psychrotolerant strain of P. griseofulvum [33]. The catalase studied was an intracellular enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, cold-adapted oxidoreductases derived from microorganisms mainly consist of sorbitol dehydrogenase, glutathione reductase, hydrogen peroxide reductase, and superoxide dismutase. Of these, cold-adapted superoxide dismutase is commonly used in clinical debridement and for other therapeutic purposes ( DangThu et al, 2020 ; Wang Z. P. et al, 2020 ; Wang Q. et al, 2020 ; Krumova et al, 2021 ). Presently, Pseudoalteromonas , Salmonella , and the fungi Aspergillus are the primary sources of cold-adapted superoxide dismutases.…”
Section: Principal Types Of Cold-adapted Enzymes From Microorganismsmentioning
confidence: 99%